An Advanced Automated Patch Clamp Protocol Design to Investigate Drug—Ion Channel Binding Dynamics - Lukacs, Peter; Pesti, Krisztina; Földi, Mátyás C.; Zboray, Katalin; Toth, Adam V.; Papp, Gábor; Mike, Arpad (Frontiers in Pharmacology, 2021)
Standard high throughput screening projects using automated patch-clamp instruments often fail to grasp essential details of the mechanism of action, such as binding/unbinding dynamics and modulation of gating. In this study, we aim to demonstrate that depth of analysis can be combined with acceptable throughput on such instruments. Using the microfluidics-based automated patch clamp, IonFlux Mercury, we developed a method for a rapid assessment of the mechanism of action of sodium channel inhibitors, including their state-dependent association and dissociation kinetics. The method is based on a complex voltage protocol, which is repeated at 1 Hz. Using this time resolution we could monitor the onset and offset of both channel block and modulation of gating upon drug perfusion and washout. Our results show that the onset and the offset of drug effects are complex processes, involving several steps, which may occur on different time scales. We could identify distinct sub-processes on the millisecond time scale, as well as on the second time scale. Automated analysis of the results allows collection of detailed information regarding the mechanism of action of individual compounds, which may help the assessment of therapeutic potential for hyperexcitability-related disorders, such as epilepsies, pain syndromes, neuromuscular disorders, or neurodegenerative diseases.